Biocompatibility of a resin-modified glass-ionomer cement applied as pulp capping in human teeth - Do Nascimento, ABL; Fontana, U. F.; Teixeira, H. M.; Costa, CAD (Mosher & Linder, Inc, 2000)
Purpose: to evaluate the human pulp response following pulp capping with calcium hydroxide (CI-I, Group 1), and the resin-modified glass-ionomer Vitrebond (VIT, Group 2). Materials and Methods: Intact teeth with no cavity preparation were used as control Group (ICG, Group 3). Buccal Class V cavities were prepared in 34 sound human premolars. After exposing the pulps, the pulp capping materials were applied and the cavities were Filled using Clearfil Liner Bond 2 bonding agent and Z100 resin-based composite. The teeth were extracted after 5, 30, and from 120 to 300 days, fixed in 10% buffered formalin solution, and prepared according to routine histological techniques. 6-mu m sections were stained with hematoxylin and eosin, Masson's trichrome, or Brown gr Brenn technique for bacterial observation. Results: At 5 days, CH caused a large zone of coagulation necrosis, the mononuclear inflammatory reaction underneath the necrotic zone was slight to moderate. VIT caused a moderate to intense inflammatory pulp response with a large necrotic zone. A number of congested venules associated with plasma extravasation and neutrophilic infiltration was observed. Over time, only CH allowed pulp repair and complete dentin bridging around the pulp exposure site. VIT components displaced into the pulp tissue triggered a persistent inflammatory reaction which appeared to be associated with a lack of dentin bridge formation. After 30 days a few histological sections showed a number of bacteria on the lateral dentin walls. In these samples the pulp response was similar to those samples with no microleakage. VIT was more irritating to pulp tissue than CH, which allowed pulp repair associated with dentin bridge formation. These results suggested that VIT is not an appropriate dental material to be used in direct pulp capping for mechanically exposed human pulps.